What is the fully factored form of the expression 16x^2 - 49y^2
1 answer:
Answer:
(4x + 7y)(4x - 7y)
Step-by-step explanation:
Rewrite 16 as 4^2
= 4^2x^2 - 49y^2
Rewrite 49 as 7^2
= 4^2x^2 - 7^2y^2
Apply the Exponent Rule Pt 1 ((a^m*b^m =(ab)^m))
= (4x)^2 - 7^2y^2
Apply the Exponent Rule Pt 2
= (4x)^2 - (7y)^2
Apply Difference of Squares Formula (( x^2-y^2 = (x + y)(x - y)
= (4x + 7y) (4x - 7y)
You might be interested in
Answer:
13
Step-by-step explanation:
![39 \div 3 = 13](https://tex.z-dn.net/?f=39%20%5Cdiv%203%20%3D%2013)
7&8 if u draw it out first it'll help by tons
Here is a video to help you with your question:
https://youtu.be/WaeD3qKc7Jc